The Potential for Sustainable Tourism Development in Small-Scale Regions: A Case Study of Sulejów Municipality - CUDNY, Waldemar; PALUCH, Justyna (Journal of Environmental Management and Tourism; Vol 15 No 4 (2024): JEMT, Volume XV, Issue 4(76), Winter 2024DO - 10.14505/jemt.v15.4(76).07, 2024)
The article addresses the critical intersection of tourism potential and sustainable tourism, focusing on a case study of the Sulejów commune, a small municipality located in central Poland. The study analyzes Sulejów's natural and cultural attractions and other elements of tourism potential and assesses their relevance for sustainable tourism development. The research employed field observations, an intercept questionnaire survey, and SWOT analysis to evaluate tourism potential, the perspectives for sustainable tourism and identify areas for improvement. The results highlight Sulejów’s significant tourism potential, with key natural attractions such as the Sulejów Landscape Park, the Pilica River, and the Sulejów Reservoir, alongside cultural historical landmarks like the Cistercian Abbey. While respondents rated tourism potential highly, challenges include inadequate accessibility, weak eco-awareness and promotion and limited support from local institutions. The study proposes a framework emphasizing pro-ecological education, sustainable infrastructure improvements, better promotion, and the use of modern technologies to market the region sustainably. The findings contribute to the understanding of sustainable tourism in smaller communities and provide a basis for broader comparisons in future research.